Looking at the World in the Light of Jubilee - Swithinbank, Hannah J (Transformation, 2019)
This article provides an introduction to the topic of reflection in this special issue - jubilee - and to the value of thinking theologically about the ways in which jubilee illuminates and provides Christian responses to the poverty and inequalities being faced by churches around the world. It also provides an introduction to the articles included in this special issue, which is edited by Tearfund in honour of its 50th anniversary.